2015
DOI: 10.1542/peds.2014-3977
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Occult Fractures in Injured Children

Abstract: OBJECTIVES: To examine variation across US hospitals in evaluation for occult fractures in (1) children ,2 years old diagnosed with physical abuse and (2) infants ,1 year old with injuries associated with a high likelihood of abuse and to identify factors associated with such variation. METHODS:We performed a retrospective study in children ,2 years old with a diagnosis of physical abuse and in infants ,1 year old with non-motor vehicle crash-related traumatic brain injury or femur fractures discharged from 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…32 Despite the fact that guidelines are readily available, a recent study in a large number of hospitals in the USA showed that there was substantial variation in the proportion of children receiving the appropriate radiological work-up after a diagnosis or high likelihood of abuse. 34 Overall, only half of all children underwent a skeletal survey, and teaching hospitals and hospitals with a high caseload of injured children performed more skeletal surveys. 34 Other studies in the USA, UK and Netherlands showed similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Despite the fact that guidelines are readily available, a recent study in a large number of hospitals in the USA showed that there was substantial variation in the proportion of children receiving the appropriate radiological work-up after a diagnosis or high likelihood of abuse. 34 Overall, only half of all children underwent a skeletal survey, and teaching hospitals and hospitals with a high caseload of injured children performed more skeletal surveys. 34 Other studies in the USA, UK and Netherlands showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…34 Overall, only half of all children underwent a skeletal survey, and teaching hospitals and hospitals with a high caseload of injured children performed more skeletal surveys. 34 Other studies in the USA, UK and Netherlands showed similar results. 31,[35][36][37] For the reporting radiologist, it is important that, just like in all other cases, the radiology request clearly states the indication for the skeletal survey, including details on current clinical problems, mode of presentation and relevant (medical-, family-and social) history.…”
Section: Discussionmentioning
confidence: 99%
“…9 Even greater variation in rates of occult fracture evaluation in this population were observed in a study of primarily non-pediatric hospitals; rates of SS performance ranged from 26% to 98% after adjusting for case mix. 10 Previous studies have also shown that among infants with similar type and severity of traumatic brain injury, infants of minority race or without private insurance were more likely to undergo SS than infants of white race or with private insurance. 7,11 Utilization of more specific guidelines for performing SS may eliminate these disparities and variations in evaluation.…”
mentioning
confidence: 97%
“…These findings suggest that implicit biases of medical providers may contribute to disproportionately high rates of child abuse evaluation and reporting for poor or African-American families, and disproportionately high rates of missed abuse in affluent, or White families. (Jenny, Hymel, Ritzen, Reinert, & Hay, 1999; Lindberg et al, 2015; Wood et al, 2012a; Wood, French, Song, & Feudtner, 2015; Wood et al, 2010)…”
Section: Discussionmentioning
confidence: 99%
“…(Bradford, Choudhary, & Dias, 2013; Christian & Block, 2009; Postema, Sieswerda-Hoogendoorn, Majoie, & van Rijn, 2014; Sieswerda-Hoogendoorn, Postema, Verbaan, Majoie, & van Rijn, 2014) Further, variable practice patterns and systems of care for medical, social and law-enforcement professionals limit the generalizability of single center results. (Hooft et al, 2015; Lindberg et al, 2015; Lindberg, Lindsell, & Shapiro, 2008; Wood et al, 2012b; Wood, 2015; Wood, 2014)…”
Section: Introductionmentioning
confidence: 99%